Consumer adoption and use of payment technology: Convenience benefits vs. security concerns - Martin Brown; Laura Felber; Christoph Meyer (Swiss National Bank, Study Center Gerzensee, 2025)
Convenience and security are the two key attributes that consumers consider when choosing between payment technologies. We examine how consumers react to an exogenous change to the convenience and security of digital payments. We study an increase in the 'tap-and-go' limit for contactless point-of-sale card payments. A higher 'tap-and-go' limit enables faster and easier verification for larger value transactions. However, a higher limit also increases security concerns, as the misappropriation of a card can lead to larger losses. Our analysis is based on anonymized transaction-level data for a large sample of debit card payments between 2019 and 2021. We reveal that the increase in the 'tap-and-go' limit caused a substantial increase in the consumer use of contactless payments, but had only a minor impact on first-time adoption. Our findings are consistent with a stylized model in which the convenience benefits of digital payments are largest for small-value on-the-fly transactions and security concerns are heterogeneous across consumers. In this framework, only consumers with weak security concerns adopt the technology and respond to subsequent improvements in its convenience.
Keywords: D14; E42; G21; G23; G50; O33; 330; Payment choice; technology adoption; contactless payments; COVID-19